Penerapan Sistem Digitalisasi UMKM Melalui QRIS, Google Maps, dan Literasi Teknologi Masyarakat : Pengabdian - Aam Amaliah; Billal Rivaldy; Ameliani Amanda; Ratna Apriyanti; Listiana Amalia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Thematic Community Service Program (Kuliah Kerja Nyata or KKN) aims to empower local communities through the implementation of digitalization systems for Micro, Small, and Medium Enterprises (MSMEs). The program includes a series of activities such as socialization, assistance in creating QRIS and Google Maps accounts, product photography training, frame design, the establishment of a live streaming studio, and digital marketing training. The results show that digitalization has a positive impact on improving MSME accessibility and marketing, although challenges in technological infrastructure still remain.